2017
DOI: 10.1080/00952990.2017.1355919
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological comparisons of cocaine versus methamphetamine users: A research synthesis and meta-analysis

Abstract: Overall, cocaine and methamphetamine users share similar neuropsychological profiles. However, cocaine appears to be more associated with working memory impairments, which are typically frontally mediated, while methamphetamine appears to be more associated with memory impairments that are linked with temporal and parietal lobe dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 140 publications
1
8
0
1
Order By: Relevance
“…On the other hand, riluzole reduced amphetamine-induced locomotion (da Silva et al, 2003) and conditioned place preference (Tzschentke and Schmidt, 1998) in rats and showed a differential effect for cocaine and methamphetamine favoring its blocking effect on the acute response to methamphetamine (Itzhak and Martin, 2000). It is noteworthy that recent comprehensive reviews and original studies have demonstrated differences between cocaine and methamphetamine in neurotransmitter alterations (Ashok et al, 2017), neuropsychological effects (Hall et al, 2018), and neurobiological response to treatments (Johnson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, riluzole reduced amphetamine-induced locomotion (da Silva et al, 2003) and conditioned place preference (Tzschentke and Schmidt, 1998) in rats and showed a differential effect for cocaine and methamphetamine favoring its blocking effect on the acute response to methamphetamine (Itzhak and Martin, 2000). It is noteworthy that recent comprehensive reviews and original studies have demonstrated differences between cocaine and methamphetamine in neurotransmitter alterations (Ashok et al, 2017), neuropsychological effects (Hall et al, 2018), and neurobiological response to treatments (Johnson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The CUD has also been related to executive dysfunctions that compromise efforts to initiate or maintain abstinence and affects the functionality and therapeutic effectiveness of patients 46 , 47 . Regarding the relationship between gender and educational level, women and men with low educational level started cocaine use much earlier than those with secondary studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since many other insults, including exposure to other substances, can alter BBB permeability, would additive physical damage of the BBB be always expected? This is not necessarily true, as METH has been shown to exert particular effects on the CNS, structurally and molecularly, even when compared to other related stimulants such as cocaine [106][107][108].…”
Section: S El Hayek Et Almentioning
confidence: 99%